PERAN DINAS SOSIAL DALAM MENANGANI KELUARGA MISKIN DI KOTA MAKASSAR - Makmur, Ferdian Utama; Mone, Ansyari; Yusuf, Muhammad (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2023)
This study aims to determine the role of the Social Service in dealing with poor families in the city of Makassar. The type of research used is qualitative descriptive type. Data collection techniques used are observation, interviews. Based on the results of research on the Role of the Social Service in Handling Poor Families in Makassar City, there are a number of things that still need to be considered because they have not been optimally handled. This can be seen from several indicators of the role of the Social Service in overcoming poor families which include: (1) Government as Regulator (2) Government as Dynamicator (3) Government as Facilitator. The role of government as regulator in handling social services for the poor in helping the community has not implemented well because the community continues to receive assistance through old data collection rather than the latest that needs to be completed. for example as a commitment to participate in all programs so that the assistance can be useful later. The government's role as dynamite in dealing with the poor is in the form of leadership.